Pro-creche Program: a case of governmental subsidy to private institutions - Costa, Beatriz Aparecida [UNESP] (Editora Univ Leopoldlanum, 2018)
We seek in this paper to present the Pro-Creche Program and its development in a medium-sized municipality in the state of Sao Paulo. The Pro-Creche Program constitutes a partnership between local governments and private for-profit institutions that take care of young children that cannot be placed in municipal schools due to a lack of vacancies. This article is the result of a master's degree research project entitled Tro-Creche' Program and the Municipal Public Service: A Look at the Teaching Offer Conditions for Early Childhood, based on a qualitative research approach and a study case methodology. In the city studied, more than 50% of public 0-3-year-old students are enrolled in private educational institutions subsidized by the government. Our literature review revealed that this mode of partnership is currently not in accordance with the existing laws, as one cannot find legal support for the establishment of partnerships between local governments and private schools.
Keywords: early childhood education; privatization of education; public-private partnership